No time for play - Carolino, Ditsi; Coronel, Sheila; Rimban, Luz.; International Labour Organization; Philippine Center for Investigative Journalism ([S.l.] PCIJ and ILO, 1996)
Examines the plight of Filipino working children and looks at what is being done to help them.
VHS.
Also available in VCD format.
Narrator, Boots Anson Roa.
Keywords: Children -- Employment -- Philippines; Sociology